Risk Reduction Strategy and Risk Management on The Basis of Quality Assessments. Issue 6 (June 2020) - Borkovskaya, Victoria; Passmore, David
Abstract: The main issue of the study is the problem of improving the efficiency of risk management of the program. The article proposes a method for determining the quality of risk assessments of a program consisting of several projects. Risk management tasks are set and solved on the basis of risk reduction and risk avoidance strategies. The aim of the study is a systematic integrated approach to the formulation and solution of tasks to improve the efficiency of the risk management program, which allows you to objectively, fully and accurately assess the relationship of economic and technical indicators. Qualitative risk assessment can be carried out by a common method of analogy, the essence of which is to analyse the totality of data on similar projects. Here they conduct a study of impact of adverse factors on them in order to accurately determine the potential risk of new projects. The main difficulty of using the methods is the exact and correct choice of analogues, since there are no formal criteria for determining the degree of similarity of situations. All aggregate socially significant economic indicators of operational measures can become the basis of legislative regulation in the industry. Conclusions: the strategy of risk reduction is that activities are carried out that reduce either the probability or damage or both from medium to low, from high to medium or low.